2023
DOI: 10.3390/nano13030518
|View full text |Cite
|
Sign up to set email alerts
|

B-Doped g-C3N4/Black TiO2 Z-Scheme Nanocomposites for Enhanced Visible-Light-Driven Photocatalytic Performance

Abstract: Black TiO2 with abundant oxygen vacancies (OVs)/B-doped graphitic carbon nitride (g-C3N4) Z-scheme heterojunction nanocomposites are successfully prepared by the one-pot strategy. The OVs can improve not only photogenerated carrier separation, but also the sorption and activation of antibiotic compounds (tetracycline hydrochloride, TC). The prepared heterojunction photocatalysts with a narrow bandgap of ∼2.13 eV exhibit excellent photocatalytic activity for the degradation of tetracycline hydrochloride (65%) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…First, we configured Wi-Fi module as Access point Bluetoothbeacon fromHC-05 shown in Figure 3 with transmit power of 20 dBm and transmit interval of 100 milliseconds. Then the RSSI value willbe deployed in this research as shown in Figure 2 represented by the blue dots as beacon deployed where on the site will be placed at 5m apart each other height from the floor Due to the simplicity on basic idea of trilateration, many researcher [7,8,10] has proposed a new idea to include other parameters that can be taken as measurement such as Time of Arrival (TOA) and Time Difference of Arrival (TDOA). TOA is the time measured for a radio wave from transmitter to reach receiver and TDOA is the measurement taken by examining the difference of time between each radio signal interval.…”
Section: Experimentaldesignmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we configured Wi-Fi module as Access point Bluetoothbeacon fromHC-05 shown in Figure 3 with transmit power of 20 dBm and transmit interval of 100 milliseconds. Then the RSSI value willbe deployed in this research as shown in Figure 2 represented by the blue dots as beacon deployed where on the site will be placed at 5m apart each other height from the floor Due to the simplicity on basic idea of trilateration, many researcher [7,8,10] has proposed a new idea to include other parameters that can be taken as measurement such as Time of Arrival (TOA) and Time Difference of Arrival (TDOA). TOA is the time measured for a radio wave from transmitter to reach receiver and TDOA is the measurement taken by examining the difference of time between each radio signal interval.…”
Section: Experimentaldesignmentioning
confidence: 99%
“…TOA is the time measured for a radio wave from transmitter to reach receiver and TDOA is the measurement taken by examining the difference of time between each radio signal interval. The most accurate usage of TOA/TDOA has been proposed by [10] where radio wave propagation was modeled as probabilistic model and determination of position will be based on timedelay estimation algorithms and this method has proven to solve the fading effect of radio wave propagation.…”
Section: Experimentaldesignmentioning
confidence: 99%
“…Electrospinning is a top‐down technique that can be used to produce nanofibers with various diameters and structures, depending on the parameters used. Coaxial, side‐by‐side and tri‐axial electrospinning is the most popular technologies, as they are capable to combine different materials to realize various functions, [ 28,29 ] including drug delivery, [ 30 ] piezophotocatalysis, [ 31 ] The technique has gained popularity in the preparation of piezoelectric thin films due to its ability to produce highly aligned nanofibers. Piezoelectric materials generate an electric charge when subjected to mechanical stress, and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…The defective TiO 2 with Ti 3+ exhibited stronger visible light absorption and much higher removal efficiency of methylene blue under visible light illumination than pristine TiO 2 [ 3 ]. Similarly, Wang et al developed B-doped g-C 3 N 4 /black TiO 2 Z-Scheme heterojunctions with enhanced charge separation efficiency and increased tetracycline sorption ability [ 4 ]. Heterojunctions with abundant defects and a bandgap of 2.13 eV could degrade 65% tetracycline hydrochloride in 30 min in the presence of visible light [ 4 ].…”
mentioning
confidence: 99%
“…Similarly, Wang et al developed B-doped g-C 3 N 4 /black TiO 2 Z-Scheme heterojunctions with enhanced charge separation efficiency and increased tetracycline sorption ability [4]. Heterojunctions with abundant defects and a bandgap of 2.13 eV could degrade 65% tetracycline hydrochloride in 30 min in the presence of visible light [4]. Some applications in bioactive coatings have also been highlighted.…”
mentioning
confidence: 99%